Use of microsatellite markers to detect heterozygosity in an F2 generation of a black rice and white rice cross - Kristamtini Kristamtini; Taryono Taryono; Panjisakti Basunanda; Rudi Hari Murti (Universitas Gadjah Mada, 2018)
The aim of this research was to know the heterozygosity of F2 generation from black rice and white rice crossing using microsatellite marker. The research material consisted of F2 Sx G plant population from black rice (S) and white rice Situbagendit (G) crosses, female parent of black rice (S), male parent of white rice (G), chemical and organic fertilizer, chemicals and tools for molecular activity and 3 microsatellite markers related to color properties (RM 220, RM 224 and RM 252). All of plant populations (generation F2, parent female, parent male) were planted in fields up to harvest. Young leaves (30 days after planting) all of plant populations were molecularly analyzed using 3 microsatellite markers (RM 220, RM 224 and RM 252). Stages of this activity include DNA isolation, PCR reaction, and visualization of PCR results using Metaphore Agarose Gel Electrophoresis. The results showed that the percentage of the number of individual plants showing heterozygous pattern in F2 S × G plant generation was 50% (RM 220); 40% (RM 224) and 60% (RM 252), so the RM 252 microsatellite marker was effectively used as a DNA-assisted selection tool on the crossbreed of black rice with white rice.